2006
DOI: 10.1163/156854006777554848
|View full text |Cite
|
Sign up to set email alerts
|

Tethys origin and subsequent radiation of the spiny lobsters (Palinuridae)

Abstract: The Palinuridae arose in the Atlantic-European region during early Mesozoic at a period of high sea level in the vast, warm 'Super Tethys' Ocean. During the Tertiary, equator-ward movements of the African, South American, and Australian Plates have subdivided the Tethys, created and expanded the Southern Ocean, and thus produced a multitude of separated environmental habitats in all the major oceans of the world. The family diverged in the Jurassic into the Stridentes group, seven genera of which survive today… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…The second major lineage included P. polyphagus of group III and P. homarus, P. versicolor, and P. ornatus of group IV. Puerulus and Linuparus of Palinuridae are two deep-sea genera (George, 2006;George & Main, 1967). All selected species of Palinuridae in the present study belong to the Stridentes (George & Main, 1967;Parker, 1884).…”
Section: Discussionmentioning
confidence: 71%
“…The second major lineage included P. polyphagus of group III and P. homarus, P. versicolor, and P. ornatus of group IV. Puerulus and Linuparus of Palinuridae are two deep-sea genera (George, 2006;George & Main, 1967). All selected species of Palinuridae in the present study belong to the Stridentes (George & Main, 1967;Parker, 1884).…”
Section: Discussionmentioning
confidence: 71%
“…Estimates in this study using fossil calibrated nodes and four loci demonstrate that Panulirus homarus rubellus might have arisen between 10–16 MYA. George (2006) suggests that the fragmentation of the Tethys Sea is responsible for the radiation of Panulirus . Studies have shown that the final closure of the Tethys seaway, 14 MYA, during the Middle Miocene, had a significant impact on global ocean circulation (Hamon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Achelata infraorder diverged into the spiny (Palinuridae) and slipper lobster (Scyllaridae) families around 250 MYA (Bracken-Grissom et al, 2014; George, 2006; Tsang et al, 2009). These authors propose that, approximately 230 MYA, the Palinuridae diverged into stridulating (sound-producing) Stridentes ( Linuparus , Justitia , Nupalirus , Palinustus , Puerulus , Palibythus, Palinurus and Panulirus ) and non-stridulating Silentes groups ( Projasus , Jasus , Sagmariasus and Palinurellus ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crown divergence of Achelata's families occurred in the Early Cretaceous and the Late Triassic, respectively (Wolfe et al, 2019). Fossil records and geographic distribution of species suggest that speciation of palinurid lobsters follows an allopatric mode (George, 2006), while this mode of speciation is not completely supported in scyllarid lobsters. This group has ecologically diversified to exploit different environments with some genera presenting scarce geographic overlap (Webber and Booth, 2007) as signal of competitive exclusion (Gittenberger, 1991;Rundell and Price, 2009), and others with parapatric distribution but subtle morphological differences that suggest low character displacement, a response for interspecific competition reflected in accentuated phenotypic differences (Brown and Wilson, 1956).…”
Section: Introductionmentioning
confidence: 99%